2005
DOI: 10.1186/bcr1345
|View full text |Cite
|
Sign up to set email alerts
|

Antisense oligonucleotides targeting the progesterone receptor inhibit hormone-independent breast cancer growth in mice

Abstract: Introduction Previous data from our laboratory suggested that progesterone receptors (PRs) are involved in progestinindependent growth of mammary carcinomas. To investigate this possibility further, we studied the effects of PR antisense oligodeoxynucleotides (asPR) on in vivo tumor growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 42 publications
3
27
0
Order By: Relevance
“…In our tumor model, we have already demonstrated that the antiprogestin onapristone was as effective as RU-486 at inducing regression of 59-2-HI, 32-2-HI and C7-2-HI tumors [36] and, furthermore, that antisense oligonucleotides of PR inhibited 32-2-HI tumor growth [39]. In the present study, we have also shown that the new antiprogestin ZK 230211 is as effective as RU-486 in inducing tumor regression.…”
Section: Discussionsupporting
confidence: 61%
“…In our tumor model, we have already demonstrated that the antiprogestin onapristone was as effective as RU-486 at inducing regression of 59-2-HI, 32-2-HI and C7-2-HI tumors [36] and, furthermore, that antisense oligonucleotides of PR inhibited 32-2-HI tumor growth [39]. In the present study, we have also shown that the new antiprogestin ZK 230211 is as effective as RU-486 in inducing tumor regression.…”
Section: Discussionsupporting
confidence: 61%
“…32-2-HI is the HI variant derived from 32-HD [36]. Both tumors express ERa, ERb, and PRs and regress with antiprogestin or estrogen treatment [42,43].…”
Section: Animalsmentioning
confidence: 99%
“…Histopathological analyses of the uterus and vagina indicated an estrogenic effect, probably due to low estrogen levels (Michna et al 1989). Similarly, we demonstrated that BALB/c mice, treated with antisense PR (asPR) oligonucleotides, showed continuous estrous (Lamb et al 2005).…”
Section: Micementioning
confidence: 66%
“…The role of the PR in the antiprogestin-induced effect was confirmed using asPR oligonucleotides to knockdown PR expression in vivo (Lamb et al 2005). These tumors may also regress with E 2 treatment (0.5-5 mg pellets), almost as well as with antiprogestin treatment.…”
Section: Contributions Of the Mpa Murine Breast Cancer Modelmentioning
confidence: 81%
See 1 more Smart Citation